Who needs credit? : poverty and finance in Bangladesh - Wood, Geoffrey D., 1945-; Sharif, Iffath (Dhaka, Bangladesh : University Press, 1997)
Contributed papers of a seminar.
Includes bibliographical references (pages 381-391) and index.
BIED
Complimentary copy from BIED
Keywords: Credit -- Bangladesh; Small business -- Bangladesh; Banks and banking -- Bangladesh; Poor -- Bangladesh